Deprescription of anti-hypertensives: An integrative literature review (Research, Society and Development, 2025)
Objective: to identify recommendations and/or processes for deprescription antihypertensive drugs in patients with Systemic Arterial Hypertension (SAH). Methodology: integrative literature review, using the Pubmed, Web of Science, Embase, Cochrane Library, Scopus and Virtual Health Library (BVS) databases. Articles in English, Spanish and Portuguese, containing an abstract in English; articles published in the last 5 years; articles with recommendations and/or processes for deprescribing antihypertensives were included. Results: 4 studies were selected that revealed the main reasons for deprescribing antihypertensives: advanced age and clinical conditions that contraindicate their use and risk of adverse reactions. The studies revealed that centrally acting antihypertensives and alpha blockers were the most reported for deprescription due to the risks of adverse effects and because they are not first-line treatment for hypertension. An algorithm for deprescribing was proposed in the following steps: patients with potential benefit from deprescription; review all antihypertensives used by the patient; assess risks and benefits; patient and family literacy on deprescription; select antihypertensives for deprescribing; monitoring by a multidisciplinary team. Conclusion: there are few studies evaluating deprescription in young or adult patients with controlled blood pressure, using monotherapy or combination of the first treatment options, lacking more evidence to recommend deprescription in these cases. The proposed algorithm is based on a restricted set of evidence and can be considered as a starting point for future investigations.